Exploring workload-related injury risk factors in elite female volleyball players - Mashimo, S.; Sakaguchi, M.; Takegami, A.; Hogan, T.; Yoshida, N. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Monitoring athletic workloads and athletes` responses is important to minimise injury risk and maximise athletic performance [1]. The relationship between workload and injury has been studied in numerous outdoor sports, such as football and rugby; however, studies on indoor sports, including volleyball, are limited [2]. This study aimed to investigate potential workload-related injury risk factors in elite female volleyball players. METHODS: From June 2022 to March 2023, 19 Japanese female volleyball players were followed prospectively. Every Sunday, injuries were measured using the Japanese version of the Oslo Sports Trauma Research Center (OSTRC) Questionnaire on Health Problems (OSTRC-H2.JP) [3]. The prevalence of all injuries and substantial injuries were calculated once weekly and presented with 95% confidence interval (CI). Workloads were monitored daily using the session rating of perceived exertion (sRPE) as the internal load and total jump height recorded by VERT 3.0 (Mayfonk Inc., Fort Lauderdale, FL, USA) as the external load. The acute:chronic workload ratio (ACWR) was calculated by dividing acute load (7-day) by chronic load (21-day and 28-day) with a rolling average (RA) and exponentially weighted moving average (EWMA) calculations and coupled and uncoupled approaches. The association between workload and injury was determined by random-effects logistic regression models. Multicollinearity was verified by variance inflation factor (VIF). RESULTS: The OSTRC-H2.JP average response rate was 85.0% throughout all weeks. The average weekly prevalence of all injuries was 51.4% [95% CI; 47.6-55.2%], of which 13.9% [95% CI; 11.0-16.9%] were considered substantial. The most affected body parts of injuries were the knee (n = 19, 15.8%), hip/groin (n = 12, 10.0%), and thigh (n = 12, 10.0%). After checking for no multicollinearity that VIF * 5, three candidate variables (7:21/internal/coupled/EWMA, 7:21/external/coupled/EWMA, 7:28/external/coupled/EWMA) were included in the random-effects logistic regression model. Adjusted odds ratios (aORs) of workload variables were 0.99 (7:21/internal/coupled/EWMA, 95%CI; 0.33-2.96), 3.84 (7:21/external/coupled/EWMA, 95% CI; 1.21-12.17), and 0.94 (7:28/external/coupled/EWMA, 95% CI; 0.38-2.36), of which "7:21/external/coupled/EWMA" was a significant injury risk factor. CONCLUSION: In this study, >50% of elite female volleyball players experienced symptoms of injury. Moreover, one in 10 participants presented substantial injuries that affected their sports participation and performance. The external workload was associated with the occurrence of injury; 7:21 ACWR if using a coupled approach and EWMA calculation. Therefore, monitoring external workload is essential to prevent injuries in elite female volleyball players.